Structure and impact of taxonomic diversity on cocoa of Soconusco, Chiapas, México - Suarez-Venero, Gicli Manuel; Avendaño-Arrazate, Carlos Hugo; Ruiz-Cruz, Pablo Amin; Estrada-de-los-Santos, Paulina (Agronomía Mesoamericana, 2019)
Introduction. The cultivation of cocoa in Mexico is an exportable item that guarantees the subsistence of thousand families. The state of Chiapas is one of the most important producers; however, even the yields are low due to different factors. These can be minimized with appropriate agroforestry design that responds to the requirements of the crop. Objective. The objective of this work was to evaluate the structure of taxonomic diversity in cocoa plantations, and analyze its influence on the crop in Soconusco, Chiapas, Mexico. Materials and methods. The research was carried out from January to May 2018 in thirteen municipalities: Cacahoatán, Tuxtla Chico, Frontera Hidalgo, Metapa, Suchiate, Tapachula, Huixtla, Tuzantán, Huehuetán, Escuintla, Acacoyagua, Acapetagua and Mapastepec. Representative plots of 50x20 m were established, in which the present species were counted and classified taxonomically. The diameter at chest height (DAP) and total height (Ht) were evaluated. An analysis was made to define the strata (lower, middle and upper) in the vertical structure of the agroforestry system, and considerations were made about the influence of the results on the cocoa. Results. 35 tree species were determined with 199 plants belonging to twenty-two families. The most important species were Cordia alliodora, Tabebuia rosea and Pouteria sapota. Conclusion. The shade tree species registered in the vertical and horizontal structure of the agroforestry cocoa systems of the Soconusco region, Chiapas, generated an excess of shade equivalent to an average in the region of 14.16 % of the total illumination, and the consequent competition for light among the species studied, including cocoa cultivation.